Effects of mix-design variables on the workability, rheology and stability of self-consolidating concrete - Alami, Mohammad Musa; Erdem, Tahir Kemal (Revista de la Construcción. Journal of Construction, 2022)
This study investigates the effects of basic mix design variables such as water/cement ratio (w/c), slump flow, coarse-to-total aggregate ratio (CA/TA), and maximum aggregate size (Dmax) on the main characteristics of self-consolidating concrete. The w/c of the mixtures was either 0.42 or 0.50. The CA/TA ranged between 0.45 and 0.53. Slump flow was adjusted to 550, 650 or 720 ±20 mm by varying the superplasticizer content. Dmax was varied as 10, 15 and 20 mm. V-funnel, L-box, rheometer, sieve segregation tests and a new test method, recently developed by the authors, for dynamic segregation resistance were performed. The effect of each variable on the test results were effectively summarized in a table. Increasing the w/c, CA/TA and Dmax decreased the superplasticizer demand and increased the flowability. When the slump flow, w/c and CA/TA were higher, viscosity was found to be lower. Higher values of CA/TA and Dmax were found to reduce the passing ability. Increasing the slump flow (or superplasticizer content), CA/TA and Dmax disturbed the stability. Generally, the effects of w/c and slump flow on the SCC characteristics were more pronounced when compared to those of CA/TA and Dmax. Good correlations were obtained between several test results.